Hubungan Peran Suami, Pengetahuan dan Peran Tenaga Kesehatan dengan Pemilihan Metode Kontrasepsi Jangka Panjang - Karkarnah Karkarnah (MPI Press, 2023)
Introduction: Contraceptive devices that have high effectiveness include the IUD and implants, which are one type of MKNP, but most women choose to use non-MKJP contraceptives. Parung Panjang Subdistrict in 2021 the number of PUS active MKJP users is 953, acceptors with the percentage of IUD use is 425 people and implants is 528. Several factors related to the selection of MKJP types of implants and IUDs include the role of the husband, knowledge and the role of health workers. Objective: The purpose of the study was to determine the relationship between the husband's role, knowledge and the role of health workers with the selection of long-term contraceptive methods in the work area of ​​the Parung panjang Health Center Bogor 2022. Methode: The research method used was quantitative analysis using a cross sectional approach using primary data, the number of samples was 91 respondents, accidental sampling technique, data analysis using Chi Square test. Result: The results of the univariate analysis that most of the MKJP selected were implants 52.8%, the husband's role was supportive 60.4%, mother's knowledge was good 83.5% and the role of health workers was good 62.6%. The results of the bivariate analysis of the husband's role (p= 0.017), knowledge (p= 0.033) and the role of health workers (p= 0.001). Conclusion: There is a relationship between the husband's role, knowledge and the role of health workers with the choice of long-term contraceptive methods.